Analysis of Financial Statements in Assessing the Financial Performance of the North Sumatra Provincial Government - Hutagaol, Junita; Irawan, Irawan (IJBLE Scientific Publications Community Inc., 2024)
Good regional financial management can affect the progress of a region. In addition, the competence of human resources and the potential of supporting natural resources can also affect it. Financial statements can also reflect how the region's finances are managed. This study aims to find out the financial performance of the North Sumatra Provincial Government from 2020 to 2023. The data analysis technique used is quantitative descriptive using the local government financial ratios which can be seen from: (1) Regional Financial Independence Ratio, (2) Regional Financial Dependency Ratio, (3) Regional Financial Decentralization Degree Ratio, (4) PAD Effectiveness Ratio, (5) PAD Efficiency Ratio, (6) Compatibility Ratio, and (7) Growth Ratio. The data collection technique used is documentation. This study uses secondary data, namely financial statements that have been audited by the Financial Audit Agency obtained from the official website of the North Sumatra Provincial Government. The results of this study are the Financial Performance of the North Sumatra Provincial Government in 2020-2023: (1) The Regional Financial Independence Ratio is included in the delegative category, with an average percentage of 103.36%. (2) The Regional Financial Dependence Ratio is included in the high category with an average percentage of 48.87%. (3) The Degree of Decentralization Ratio is included in the very good category with an average percentage of 50.51%. (4) The PAD Effectiveness Ratio is included in the category of quite effective with an average percentage of 95.32%. (5) The PAD Efficiency Ratio is included in the inefficient category with an average percentage of 90.81%. (6) The Compatibility Ratio is included in the good category with an average percentage of 61.60% for operating expenditure and 12.99% for capital expenditure. (7) The Growth Ratio is included in the good/positive category with an average percentage of 5.87% PAD growth and 7.65% regional expenditure growth.